Exploring the Impact of Female Participation on Innovation Within Indonesian SOEs - Kuntadi, Yahya Agung; Lubis, Atur Tetty (EQUILIBRIUM - Jurnal Bisnis dan Akuntansi, 2025)
State-owned enterprise (SOEs) in Indonesia increasingly recognize the importance of innovation for competitiveness. Gender diversity is a key driver, with research highlighting the positive impact of women on creativity and problem-solving. This study explores how female participation in innovation initiatives within Indonesian SOEs. We examine data from 133 innovation competition records, focusing on team composition (female presence vs no female) and innovation characteristics (orientation, benefit, type, deliverable and area of focus). Chi-square tests assess overal and individual associations, while Benjamin-Hochberg (BH) correction accounts for multiple comparisons. Our findings reveal a statistically significant association between female-led teams and the specific area of focus chosen for innovation projects. This suggests women might prioritize or excel in certain innovation areas within Indonesian SOEs. Further research can explore the reason behind this association and its implication for fostering a more diverse and innovation environment in SOEs.